Inheritance of resistance to race 1 of Pseeudomonas syringae PV. Phaseolicola in some varieties of beans - Asensio, C.=700 1 Martin, E.; Montoya, J.L.
(Es, En)
ilus., 19 ref.
Keywords: PSEUDOMONAS SYRINGAE; PHASEOLUS VULGARIS; RESISTENCIA A LA ENFERMEDAD; HERENCIA GENETICA; ESPAÑA